Suitable Site Selection for Ocean Thermal Energy Conversion (OTEC) systems - A case study for Pakistan - Nadeem, Talha Bin; Naqvi, Asad A.; Ahmed, Ahsan (TECCIENCIA, 2022)
In developing countries such as Pakistan, the issue of generating power is crucial. As conventional power sources (fossil fuels) are depleting at an alarming rate. An abundant amount of energy is generated by thermal power plants using fossil fuels as their primary energy resource for combustion. Hence extreme uses of fossil fuels are noticed, which is greatly responsible for damaging our environment. Oceans exists around 71% of the surface area of earth and it has enormous potential for electricity generation. This study focuses on site selection for harnessing ocean energy by utilizing Ocean Thermal Energy Conversion (OTEC) systems for coastal areas of Pakistan. In this study, four sites across the coastal region of Pakistan have been studied namely Karachi, Gwadar, Ormara and Pasni. Their theoretical maximum Carnot efficiencies have also been determined and Gwadar has been identified as the most suitable location for OTEC plant with the maximum theoretical efficiency of around 6.53%, 6.93% and 7.75% at the cold-water depths of 1000m, 1200m and 1500m, respectively.